RANCANG BANGUN ALAT DESTILASI PADA LABORATORIUM BIOPROSES - Puspitasari; Sakius Ruso; Juliati; Dina Desriany, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Distillation is the technique of separating a liquid from its solution based on the difference in boiling point. Distillation is divided into simple, fractional, vacuum, and azeotropic distillations. The factors that influence the distillation process are the temperature of the heating water and the condenser cooling water. A bioprocess laboratory is a combination of biology and chemistry in which a variety of processes are carried out, including biological processes. The design of the distillation device is made of an iron frame, while the flask and the condenser are made of glass. Heat source using a heating jacket. The aim of this research is to design and make an effective and efficient distillation tool, selecting the type of material that is effective.